Development of 2D Animation-Based Folklore As Learning Media - Leonardo Parabang; Melda Agnes Manuhutu; Abraham Manuhutu; Natasya Virginia Leuwol; Lulu Jola Uktolseja; Jalmijn Tindage (IJISTECH (International Journal of Information System and Technology), 2022)
Multimedia is currently experiencing developments, not only for entertainment only through audio and visuals. In today's competitive economy, multimedia has a big role in marketing and advertising products and services in order to attract people to use and buy products and services. Multimedia has many types such as video, audio, text, and even animation. 2D animation is currently classified as a type of multimedia that is difficult to make but has excellent results in the teaching and learning process, therefore in this paper, we will create 2D animation about Tambrauw folklore in the learning process. This 2D animation tool used is Adobe software, starting from audio management (Adobe Audition), vector creation (Adobe Illustrator), moving objects (Adobe After Effect), and editing (Adobe Premiere Pro) to the rendering stage (Adobe Media Encoder). The expected result of making the 2D animation of Tambrauw folklore as a medium of learning is to make the learning process more effective. In addition, another goal of making the 2D animation of Tambrauw folklore as a learning medium so that folk tales originating from the land of Papua do not die from being swallowed up by the times because they are not documented.